The Effect of Photographic Image Media on Students’ Poetry Writing Skills - Mulkan Andika Situmorang; Dedi Satriawan; Namira Fitria; Ria Wuri Andary; Khairullah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study investigates the effect of photographic image media on students’ poetry writing skills, aiming to determine whether visual-based learning can enhance creativity and writing performance. The research was conducted with 57 Grade VII students during the 2023/2024 academic year using a quasi-experimental design and a simple random sampling technique. The participants were divided into two groups: 30 students in the experimental class, who learned poetry writing through photographic image media, and 27 students in the control class, who received conventional instruction. Data were collected through pretests and posttests to measure students’ poetry writing skills. The results revealed that the experimental class achieved a higher average posttest score (73.17) compared to the control class (51.85). The improvement in the experimental group (57.35%) was considerably greater than in the control group (29.01%). Statistical analysis using a paired sample t-test indicated a significance value of 0.001, which is lower than the standard alpha level of 0.05. Therefore, the null hypothesis (H₀) was rejected, confirming that the use of photographic image media had a significant positive effect on students’ poetry writing skills. The findings suggest that photographic image media can be a powerful instructional tool for teaching poetry writing. By stimulating imagination and visual thinking, this medium helps students express emotions, select appropriate diction, and develop creative ideas more effectively. The study contributes to the field of language education by demonstrating the practical value of integrating visual learning aids to improve students’ engagement and achievement in poetry writing.